Choroid Plexus Carcinoma of Third Ventricle: A Rare Case Report - Awasthi, Shivali; Kinra, Prateek; Verma, Nisha (Annals of Pathology and Laboratory Medicine, 2021)
Choroid plexus tumors are very rare tumors accounting for 0.5% of all brain tumors. They most commonly occur in childhood and present with features of raised intra-cranial pressure. World Health Organization (WHO) classifies them into 3 broad categories namely papilloma (grade 1), atypical papilloma (grade 2) and carcinoma (grade 3). These tumors are most commonly seen in the supratentorial compartment with lateral ventricle followed by third ventricle, being the most common site. Rarely, they may present in infratentorial region in adults. Dissemination through cerebrospinal fluid space is the inevitable natural course of the disease. Treatment requires total surgical resection with adjuvant chemoradiotherapy being controversial. In this study, we present a case of 7-year-old child who visited to the out-patient department of our center with progressive quadriparesis and altered sensorium and on imaging was found to have a well-defined, lobulated mass lesion with intense post contrast enhancement in posterior part of third ventricle with resultant obstructive hydrocephalus. The patient underwent craniotomy and on immuno-histopathological examination was diagnosed as a case of choroid plexus carcinoma. However, the patient succumbed to his illness a month after his surgery. The aim of this report is to highlight a rare entity, its diagnostic challenge and effect of early management in the form of surgery and chemo-radiotherapy.